2015
DOI: 10.1080/09585192.2015.1088886
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management, social connectedness and health and well-being of older and retired men: the role of Men’s Sheds

Abstract: Human resource management, social connectedness and health and wellbeing of older and retired men: The role of Men's Sheds ABSTRACT This study analyses human resource management in Men's Sheds in Australia. Men's Sheds are volunteer-based, not-for-profit, grassroots community organisations that provide health related resources and an avenue for largely older and retired men to engage with each other and the community. The research is timely given the escalating numbers of retired men and rising national health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…For instance, Liao et al (2009) indicate that the HR practices reported by employees were not as similar to those of managers as the latter would like them to be. Across studies of perceived HR content (Ang, Bartram, McNeil, Leggat, & Stanton, 2013;Ang et al, 2017;Aryee et al, 2012;Choi, 2019;Den Hartog et al, 2013;Elorza, Aritzeta, & Ayestaran, 2011;Elorza, Harris, Aritzeta, & Balluerka, 2016;Jensen et al, 2013;Jiang et al, 2017;Li & Frenkel, 2017;Liao et al, 2009;Vermeeren, 2014), the average correlation between manager and employee perceptions of HR content is moderate (r ¼ 0.37 on average). However, the size of the HR perception gap between managers and employees may differ.…”
Section: Major Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Liao et al (2009) indicate that the HR practices reported by employees were not as similar to those of managers as the latter would like them to be. Across studies of perceived HR content (Ang, Bartram, McNeil, Leggat, & Stanton, 2013;Ang et al, 2017;Aryee et al, 2012;Choi, 2019;Den Hartog et al, 2013;Elorza, Aritzeta, & Ayestaran, 2011;Elorza, Harris, Aritzeta, & Balluerka, 2016;Jensen et al, 2013;Jiang et al, 2017;Li & Frenkel, 2017;Liao et al, 2009;Vermeeren, 2014), the average correlation between manager and employee perceptions of HR content is moderate (r ¼ 0.37 on average). However, the size of the HR perception gap between managers and employees may differ.…”
Section: Major Findingsmentioning
confidence: 99%
“…One way to enhance the instrumental relevance of employee HR perception research is to pay more attention to the drivers of employee HR perceptions. In our review, 82 empirical studies examined the consequences of employee perceptions of HR practices, while only 20 investigated the factors that shape employee perceptions of HR practices (Ang et al, 2013;Ang et al, 2017;Aryee et al, 2012;Bos-Nehles & Meijerink, 2018;Choi, 2019;Chacko & Conway, 2019;Elorza et al, 2011;Elorza et al, 2016;Den Hartog et al, 2013;Heffernan & Dundon, 2016;Hewett et al, 2019;Jensen et al, 2013;Jiang et al, 2017;Li & Frenkel, 2017;Makhecha, Srinivasan, Prabhu, & Mukherji, 2018;Piening, Baluch, & Ridder, 2014;Sumelius, Bj€ orkman, Ehrnrooth, M€ akel€ a, & Smale, 2014;Van de Voorde & Beijer, 2015;Vermeeren, 2014;Webster & Beehr, 2013). The recent review by Hewett et al (2018) acknowledge the lack of understanding regarding the antecedents of HR perception.…”
Section: Enhancing Practical Relevancementioning
confidence: 99%
“…Authors suggest a causal chain approach be adopted as an analytical approach, as the impact of HR practices is complex, with many latent and mediating factors e.g. Ang et al (2017). Torre (2012) argues that a more tailored approach is required, as the context in which the practices are introduced and the needs of the individual must be considered.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Multifunctional autonomy also provides various community roles for retired men, which can help them sustain their sense that life is worth living [ 24 ]. In general, men tend to lose a sense of functionality after retirement because they previously dedicated their lives to their jobs [ 25 ]. As such, retired men may not have hobbies, the lack of which can increase the risk of depression and dementia [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, men tend to lose a sense of functionality after retirement because they previously dedicated their lives to their jobs [ 25 ]. As such, retired men may not have hobbies, the lack of which can increase the risk of depression and dementia [ 25 , 26 , 27 ]. This study showed that older men benefit by working for their communities, through multifunctional autonomy, which may prevent the deterioration of their mental faculties.…”
Section: Discussionmentioning
confidence: 99%